Effect of certain soil fungi on Metarhizium and Beauveria spp and their pathogenicity against Holotrichia consanguinea - and c.P.S. YADAVA, SHASHI SHARMA, R.B.L. GUPTA (Indian Phytopathology, 2002)
A total of 16 soil fungi were tested for their antagonistic effects to Metarhizium anisopliae, Beauveria brongniartii and B. bassiana, and for their pathogenic ability against H. consanguinea. The fungi isolated from the soil were Fusarium moniliforme [Gibberella fujikuroi], F. chlamydosporum, F. oxysporum, F. solani, Aspergillus niger, Aspergillus flavus, Aspergillus chevalieri, Curvularia lunata [Cochliobolus lunatus], Paecilomyces sp., Penicillium sp., Trichoderma viride, Alternaria alternata, Rhizopus sp., Rhizoctonia bataticola [Macrophomina phaseolina], M. phaseolina and Colletotrichum sp. Out of these species, 8 were mildly pathogenic to H. consanguinea (G. fujikuroi, F. chlamydosporum, F. oxysporum, Aspergillus niger, Aspergillus chevalieri, T. viride, Penicillium sp. and R. bataticola). Penicillium was the most antagonistic towards the pathogenic fungi.